2011
DOI: 10.15835/nsb336073
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of ABO and Rh Blood Groups in Backward Caste Population of Uttar Pradesh, India

Abstract: A series of glycoproteins and glycolipids on red blood cell surface constitute blood group antigens. These are AB, A, B and O in ABO blood group system and Rh in rhesus blood group system. A total of 1065 unrelated Backward Caste (OBC) individuals from Uttar Pradesh were studied for the phenotype and allele frequency distribution of ABO and Rh (D) blood groups. Total 1065 samples analyzed, phenotype B blood type has the highest frequency 36.81% (n=392), followed by O (32.68%; n=348), A (23.66%; n=252) and AB (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(51 reference statements)
2
5
0
Order By: Relevance
“…8 However, some other studies reported blood group A to be the most frequent among males, while blood group B has the highest frequency among females. 14,15 Most of the male and female students were found to have rhesus positive blood group as also reported by previous studies. 6,8 This shows that inheritance of ABO and rhesus blood groups are not sex-linked.…”
Section: Discussionsupporting
confidence: 82%
“…8 However, some other studies reported blood group A to be the most frequent among males, while blood group B has the highest frequency among females. 14,15 Most of the male and female students were found to have rhesus positive blood group as also reported by previous studies. 6,8 This shows that inheritance of ABO and rhesus blood groups are not sex-linked.…”
Section: Discussionsupporting
confidence: 82%
“…This corroborates with findings of previous studies that reported similar pattern of ABO blood group distribution among both sexes (Enosolease & Bazuaye, 2008). However, some other studies reported blood group A to be the most frequent among males, while blood group B has the highest frequency among females (Ghobadian, 2014, Rai & Kumar, 2011. Most of the male and female students were found to have rhesus positive blood group as also reported by previous studies (Nwuche & Ejele, 2004;Enosolease & Bazuaye, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Blood group B is most common blood group followed by blood group O, whereas blood group AB is least common among the populations of Eastern Uttar Pradesh region. To test if our sampling had covered the representative blood group distribution of this region, we referred to the published data of the same region [36][37][38][39][40][41][42][43] and performed a regression analysis. The adjusted R square value (83.6 % +3.4 %) demonstrated significantly high level of correlation between our data as well as published data, suggesting that our sampling indeed represented the regional distribution of the blood groups.…”
Section: Resultsmentioning
confidence: 99%
“…1). We have also collected blood group data of the same region for comparison from published sources [36][37][38][39][40][41][42][43].…”
Section: Methodsmentioning
confidence: 99%